2020
DOI: 10.1186/s13063-020-4223-5
|View full text |Cite
|
Sign up to set email alerts
|

Reporting of health equity considerations in cluster and individually randomized trials

Abstract: Background: The randomized controlled trial (RCT) is considered the gold standard study design to inform decisions about the effectiveness of interventions. However, a common limitation is inadequate reporting of the applicability of the intervention and trial results for people who are "socially disadvantaged" and this can affect policy-makers' decisions. We previously developed a framework for identifying health-equity-relevant trials, along with a reporting guideline for transparent reporting. In this study… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
20
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 29 publications
(23 citation statements)
references
References 40 publications
3
20
0
Order By: Relevance
“…The high number of White participants, as well as the large number of studies that did not report ethnicity ( n = 30, 44%), may limit the ability to generalize findings to other race and ethnicity groups. Similar to findings in this review, this has been a persistent challenge in the larger world of clinical trials [ 95 ], including in rehabilitation medicine [ 96 ]. This lack of inclusion for historically or socially marginalized groups may undermine personalized medicine efforts and contribute to the persistence of health inequities [ 97 ].…”
Section: Discussionsupporting
confidence: 70%
“…The high number of White participants, as well as the large number of studies that did not report ethnicity ( n = 30, 44%), may limit the ability to generalize findings to other race and ethnicity groups. Similar to findings in this review, this has been a persistent challenge in the larger world of clinical trials [ 95 ], including in rehabilitation medicine [ 96 ]. This lack of inclusion for historically or socially marginalized groups may undermine personalized medicine efforts and contribute to the persistence of health inequities [ 97 ].…”
Section: Discussionsupporting
confidence: 70%
“…This is the first comprehensive assessment of the reporting of social deprivation measures in musculoskeletal trials. Social deprivation indices and measures of social deprivation are also poorly reported in non‐musculoskeletal trials (Callander & McDermott, 2017; Malmivaara, 2019; Petkovic et al, 2020). Measures that are most frequently reported in musculoskeletal trials are similar to those reported in non‐musculoskeletal trials, namely education level, employment status and salary.…”
Section: Discussionmentioning
confidence: 99%
“…RCTs will be included in the initial title and abstract screening if the RCT authors identify their participants as a disadvantaged group concordant with one or more of the following PROGRESS-Plus criteria: place of residence, race/ethnicity/culture/language, occupation, gender/sex, religion, education, socioeconomic status, and social capital [14,15,[19][20][21][22][23]. Due to the terminologic complexity regarding disadvantaged status, author framing of disadvantage using terms such as "vulnerable," "hard-to-reach," or "underserved" will merit inclusion.…”
Section: Types Of Participantsmentioning
confidence: 99%
“…In the context of this study, we operationalize one commonly used term, the construct of "disadvantage," in relation to RCTs. We define disadvantage as social, cultural, or financial disparities that imply environmental, historical-structural, or social restriction to opportunities for health [14,15,[19][20][21][22][23]. We recognize that disadvantage may involve one or more specific attributes, contexts, or group types.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation